Tailoring Particle‐Enzyme Nanoconjugates for Biocatalysis at the Organic‐Organic Interface - Sun, Zhiyong; Cai, Meng; Hübner, René; Ansorge‐Schumacher, Marion B.; Wu, Changzhu (ChemSusChem, 2020)
Abstract Nonaqueous Pickering emulsions (PEs) are a powerful platform for catalysis design, offering both a large interface contact and a preferable environment for water‐sensitive synthesis. However, up to now, little progress has been made to incorporate insoluble enzymes into the nonaqueous system for biotransformation. Herein, we present biocatalytically active nonaqueous PEs, stabilized by particle‐enzyme nanoconjugates, for the fast transesterification and esterification, and eventually for biodiesel synthesis. Our nanoconjugates are the hybrid biocatalysts tailor‐made by loading hydrophilic Candida antarctica lipase B onto hydrophobic silica nanoparticles, resulting in not only catalytically active but highly amphiphilic particles for stabilization of a methanol‐decane emulsion. The enzyme activity in these PEs is significantly enhanced, ca. 375‐fold higher than in the nonaqueous biphasic control. Moreover, the PEs can be multiply reused without significant loss of enzyme performance. With this proof‐of‐concept, this system can be expanded for many advanced syntheses using different enzymes in the future.